Review on Digital Signal Processing (DSP) Algorithm for Distributed Acoustic Sensing (DAS) for Ground Disturbance Detection - Hafiz Zulhazmi Jabidin; Siti Azlida Ibrahim; Mohd Saiful Dzulkefly Zan; Siti Musliha Aishah Musa; Amilia Mansoor; Ngo , Hong Yeap; Nurul Ain Abdul Aziz; Choo, Kan Yeep; Ahmad Ashrif A. Bakar; Mohd Ridzuan Bin Mokhtar; Tee, Connie; Hairul Azhar Abdul-Rashid (International Journal of Integrated Engineering, 2024)
Fiber break because of third-party intrusion has become one of the challenges in maintaining the fiber-based communication link, especially those buried underground. Hence, we investigate the feasibility of using Distributed Acoustic Sensing (DAS) system to sense possible surrounding activities that might cause fiber break. This paper reviews the current digital signal processing (DSP) algorithm used in the DAS system designed to detect ground disturbance, highlighting the specific design parameters for each technique. These parameters include identification rate, classification accuracy, detection accuracy, training time, and signal-to-noise ratio (SNR). The algorithms used are near-field beamforming, phased-array beamforming, image edge detection, gaussian mixture model (GMM), gaussian mixture model - hidden Markov model (GMM-HMM), faster region-based convolutional neural networks (R-CNN), transfer learning, dual-stage recognition network, group convolutional neural network (100G-CNN), and support vector machine (SVM). By reviewing the existing techniques used in the DAS system for ground disturbance detection, we can determine the best DSP algorithm that should be implemented for fiber break prevention, enabling us to design a DAS system specifically for it in the near future.